Everyday Life at Bjerre Site 7, a Late Bronze Age House in Thy, Denmark. (August 2022) - Earle, Timothy; Olsen, Anne-Louise Haack; Eriksen, Berit Valentin; Henriksen, Peter Steen; Kristensen, Inge Kjær
Abstract : Bjerre 7 is a modest Late Bronze Age house in Thy, Denmark. Excellent preservation and full-recovery techniques provided comprehensive evidence of farm self-sufficiency, local exchange, and amber collection for trade. Spatial analyses of ceramics, lithics, plant macrofossils, and amber identified distinctive activity areas at both ends of the house and outside. Routines are discussed for refuse disposal, ceramic use in everyday activities, ad hoc knapping and use of flint tools, plant processing, and amber storage. The household was economically generalized and largely self-sufficient, with limited specialization. Located close to the North Sea, the householders collected raw amber for trade. Metal was obtained from outside for a small-scale, household industry. Although some division of labour is likely, it seems that the whole household engaged in the diverse activities identified on site.